(untitled) (International Journal of Engineering and Computer Science, 2015)
Storing of confidential data has become a most important thing these days. It is necessary that the data stored must remain secured and should be accessed at the client’s request. Cloud computing helps us to store our files on the cloud. Hence it is very efficient and helpful for a client’s point of view. But there are some security issues in this type of data storage. Thus by using encryption and decryption techniques we can encrypt and decrypt the files as per the need of the client.